Interpreting Islam : Bandali Jawzi's Islamic intellectual history - Sonn, Tamara, 1949- (Oxford University Press, 1996)
In this book, Tamara Sonn provides the first English translation of The History of Intellectual Movements in Islam (1928), a seminal text of Arab modernism written by the Palestinian intellectual Bandali al-Jawzi (1871-1942). In that book, Jawzi offered the first Marxist interpretation of the history and development of Islamic thought. The continuing importance of his work lies in Jawzi's critical method of reevaluating both European "orientalism" and classical Muslim heresiography. Fifty years before Edward Said's landmark Orientalism, Jawzi identified the source of weakness in both as concern for vested imperial interest. Sonn's translation brings to life his skillful and entertaining critique. Her introduction places Jawzi's thought in context with both postmodern intellectuals and Muslim reformists who continue the struggle to apply Islamic principles to contemporary life